2017
DOI: 10.15288/jsad.2017.78.140
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Matching Hypothesis for Emerging Adults in Project MATCH: During-Treatment and One-Year Outcomes

Abstract: ABSTRACT. Objective: Compared with older adults, emerging adults (18-29 years old) entering treatment typically have less severe alcohol use consequences. Also, their unique clinical presentations (e.g., modest initial abstinence motivation) and developmental contexts (e.g., drinkingrich social networks) may make a straightforward implementation of treatments developed for adults less effective. Yet, this has seldom been examined empirically. This study was a secondary analysis of Project MATCH (Matching Alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…These counterintuitive differences with prior literature could reflect differences in coding of comparison conditions, or that MI may be more efficacious than some other treatments. For example, Davis and colleagues (2017) found that EAs randomized to Twelve Step Facilitation treatment in Project MATCH had poorer initial outcomes compared with those receiving MI. Thus, although direct comparisons here yielded no differences between MI and CBT, or MI and PTs coded as Miscellaneous, our sample size may have precluded finding significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These counterintuitive differences with prior literature could reflect differences in coding of comparison conditions, or that MI may be more efficacious than some other treatments. For example, Davis and colleagues (2017) found that EAs randomized to Twelve Step Facilitation treatment in Project MATCH had poorer initial outcomes compared with those receiving MI. Thus, although direct comparisons here yielded no differences between MI and CBT, or MI and PTs coded as Miscellaneous, our sample size may have precluded finding significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…EAs represent one-quarter of all heroin users in the U.S. and 34% of treatment admissions (SAMHSA, 2014). Further, EAs’ treatment outcomes are worse than those for adolescents (Smith, Godley, Godley, & Dennis, 2011) or older adults (Davis, Bergman, Smith, & Kelly, 2017) necessitating additional research focus.…”
mentioning
confidence: 99%
“…For young adult males, either TAU or MET/CBT or CBT alone may be preferred treatment approaches. Yet, recent work using Project MATCH data has shown that young adults assigned to 12-step treatments have significantly worse outcomes compared with their young adult and older adult counterparts receiving MET/CBT or CBT alone (Davis, Bergman, Smith, & Kelly, 2017). Several studies have provided evidence suggesting that men and women vary in their patterns of treatment utilization (see Greenfield et al, 2007 for a review), with men having more negative attitudes toward seeking help, and being less likely to seek formal help (Oliver, Pearson, Coe, & Gunnell, 2005) or initiate treatment (Pederson & Vogel, 2007; J.…”
Section: Discussionmentioning
confidence: 99%
“…Despite previous research examining age differences on sociodemographic and drug‐related variables among opioid users, several important gaps remain. First, some studies only examined age differences among women 8‐10 . Second, those studies that included both men and women did not examine gender differences 3‐7 .…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics may contribute to continued illicit opioid use during treatment and lower levels of buprenorphine treatment retention; however, not all studies have found buprenorphine treatment outcomes differ between emerging and older adults 7 . Large studies have demonstrated that emerging adults have inferior treatment retention and outcomes when compared with other age groups in multiple contexts, for example, with treatment outcomes for alcohol in comparison to older adults 8 and adolescents, 9 as well as higher rates of drug dependence and higher psychiatric symptoms compared with older adults 10 . Related to opioid use disorder (OUD), emerging adults enter treatment with more severe employment, legal, and psychiatric problems compared with older adults 7 …”
Section: Introductionmentioning
confidence: 99%